Phenomenology in nursing research: reflection based on Heidegger's hermeneutics - Raúl Fernando Guerrero-Castañeda; Tânia Maria de Oliva Menezes; Marta Lenise do Prado
Abstract Objective: To reflect on the use of phenomenological analysis in nursing research through the hermeneutical circle of Martin Heidegger. Method: Theoretical reflection based on Martin Heidegger's concepts through literature review. Results: Phenomenology is a philosophical referential to address lived phenomena; Heidegger emphasizes the essence of being in the world bound in experiences, the hermeneutical circle is a methodological referential of analysis to understand the world lived by the being through a pre-understanding; an understanding and an interpretation to reveal the essence of the phenomenon. Conclusions and implications for practice: Nursing can make use the hermeneutic circle to understand, from a philosophical view, the phenomena in the language of those who experience them, to unveil them and to understand the subjectivity of care.